Homo Charismaticus in German and Ukrainian Appellative Discourses (A Contrastive Perspective) - Petlyuchenko, N. V. (Cognition, Communication, Discourse, 2018)
This article focuses on a discourse research into the political charisma phenomenon by means of contrastive analysis of appellative instruments of contemporary German and Ukrainian political figures – Joschka Fischer, Gerhard Schroeder, Angela Merkel, Viktor Yushchenko, Viktor Yanukovich, and Yulia Timoshenko. It reveals contrastive features of verbal, prosodic and kinetic appellativity of public figures representing two different language cultures. In the period of social crisis such political figures are defined as homo charismaticus forming a charismatic sub-discourse within the framework of political discourse.